Acneiform Eruptions Caused by Lithium Treatment May Be Related to Demodex Mites (Prostigmata: Demodecidae): A Hypothesis - Rif S. El-Mallakh; Masoud Doroodgar; Mehak Pahwa; Omar H. A. Elsayed (Biology)
Acneiform eruptions are a common adverse effect of lithium treatment that may impact adherence. It is not clear why lithium may worsen these lesions and treatment has focused on traditional treatments for acne. Demodex mites are known to commensurably exist in a large fraction of humans and are known to cause dermatologic conditions in a minority of individuals. An association with acneiform eruptions is well documented but is generally believed to not be causative. We present a hypothesis that lithium treatment may alter the environment of Demodex mites in a fashion that may increase their propensity to cause disease. If that is accurate, treatment with acaricidal agents may be an additional option.